PENGARUH KEGIATAN ECOPRINT TERHADAP KEMAMPUAN MENGENAL KONSEP POLA ABC-ABC PADA ANAK USIA 4-5 TAHUN - Syahira Adelia Jasmine; Sri Widayati (TARBAWI : Journal on Islamic Education, 2025)
This research was conducted based on observations at Kindergarten Khadijah Surabaya. Based on observations, the ability of children aged 4-5 years at Khadijah Kindergarten to implement pattern concepts is still lacking. For example, when playing the string activity, children need to sort the green, red and yellow beads repeatedly. Children still have difficulty estimating the order of the beads, the order should be red, yellow, green, children sort them into red, green, yellow. Apart from that, activities to introduce or stimulate children's ability to recognize patterns are also too monotonous, so new activity innovations are needed for children. The aim of this research is to determine the influence of ecoprint activities on the ability to recognize pattern concepts in children aged 4-5 years. This research uses a quantitative type of research, with a Pre-experiment Design in the form of One Group Pre-test Posttest Design. Ecoprint activity is a batik activity by transferring the natural colors and shapes of plants onto white cloth. Ecoprint activities are usually used to stimulate children's creativity, but this activity can also be used to introduce learning concepts such as the concept of patterns. Pattern concept material can be included in the formation of ecoprint motifs. The ecoprint activity is a treatment activity given before the post-test and after the pre-test. Based on the Wilcoxon test data analysis using SPSS 25, the asymp.Sig (2-tailed) results were 0.03 or p < 0.05 or 0.03 < 0.05. The results show that if the significance is smaller than 0.05, Ho is rejected and Ha is accepted, which means that there is an influence from ecoprint activities on the ability to recognize the concept of ABC-ABC patterns in children aged 4-5 years. The effect of ecoprint activities is that children are able to sort and arrange objects based on shape and color repeatedly